Strong ambipolar‐driven ion upflow within the cleft ion fountain during low geomagnetic activity. Issue 7 (19th July 2016) - Shen, Yangyang; Knudsen, David J.; Burchill, Johnathan K.; Howarth, Andrew; Yau, Andrew; Redmon, Robert J.; Miles, David M.; Varney, Roger H.; Nicolls, Michael J.
Abstract: We investigate low‐energy (<10 eV) ion upflows (mainly O + ) within the cleft ion fountain (CIF) using conjunctions of the Enhanced Polar Outflow Probe (e‐POP) satellite, the DMSP F16 satellite, the SuperDARN radar, and the Resolute Bay Incoherent Scatter Radar North (RISR‐N). The SEI instrument on board e‐POP enables us to derive ion upflow velocities from the 2‐D images of ion distribution functions with a frame rate of 100 images per second, and with a velocity resolution of the order of 25 m/s. We identify three cleft ion fountain events with very intense (>1.6 km/s) ion upflow velocities near 1000 km altitude during quiet geomagnetic activity ( K p < 3). Such large ion upflow velocities have been reported previously at or below 1000 km, but only during active periods. Analysis of the core ion distribution images allows us to demonstrate that the ion temperature within the CIF does not rise by more than 0.3 eV relative to background values, which is consistent with RISR‐N observations in the F region. The presence of soft electron precipitation seen by DMSP and lack of significant ion heating indicate that the ion upflows we observe near 1000 km altitude are primarily driven by ambipolar electric fields. DC field‐aligned currents (FACs) and convection velocity gradients accompany these events. The strongest ion upflows are associated with downward current regions, which is consistent with some (although not all) previously published results. The moderate correlation coefficient (0.51) between upflow velocities and currents implies that FACs serve as indirect energy inputs to the ion upflow process. Key Points: Observations of very intense (>1.6 km/s) ion upflow velocities within the cleft ion fountain near 1000 km during quiet times ( Kp < 3) The core ion distributions analysis implies less than 0.3 eV increase in ion temperature, which is consistent with RISR‐N observations The presence of intense soft electron precipitation and lack of significant ion heating suggest ambipolar electric field as the main driver